Kebijakan Moneter dalam Presfektif Ekonomi Islam Pada Pembangunan Ekonomi - Dewi Maharani (Jurnal Keislaman, 2023)
Islamic economics is required to be able to contribute to the global economy. This paper aims to analyze monetary policy in the perspective of Islamic economics in view of the country's economic development. Monetary policy is a branch of economics that influences the country's economy. Monetary in Islam not only emphasizes the supply and demand for money, but also the principle of equity, equality and creating a fair distribution of wealth and income. This study uses literature studies, namely theoretical studies and references related to values, culture and norms that develop in the social situations studied. In this research, the writer chose to study literature or study literature by collecting reference books related to research. This research study is the implication of Islamic monetary policy on economic development in Indonesia. Monetary policy can maintain economic stability by balancing the amount of money in circulation widely and in balance. If any money in circulation is greater or less than a number of goods and services, then the economy in a country will have a negative impact.